Impact of Hearing Impairment on Mental Health in Elderly Partners: Life Sciences-Audiology & Clinical Pyscology - Jha, Vivek Kumar; Kapoor, Puneet (International Journal of Life Science and Pharma Research, 2022)
Communication is one of the important way to express and share the ideas and feeling. For effective communication, hearing plays an important role. A person having problem with hearing have difficulty in day to day life, which create several misunderstandings. This study, emphasizes how hearing loss can create poor mental health for an individual or partners. This study was conducted to determine the mental health of elderly couples having hearing impairment. The need of the study is to detect the association between hearing loss and mental health. To carry out the study, the subjects were tested (Audiological Evaluation) and the mental health checklist (MHCL) was used. The audiological assessment consisted of pure tonal audiometry (PTA), carried out in a sound-treated room, air conduction (from 250 Hz to 8000 Hz), and the bone conduction threshold (500 Hz to 4000 Hz) conduction hearing threshold calculation using the Alps 2000 AD brand audiometer. With the help of IBMSPSS( Version-21) software, statistical analysis was used. For statistical analysis, the Pearson correlation was used. However, the gravity of the signs of change was shown to be positive. The result showed the main effect of group (i.e., individual with hearing impairment with hearing aids, hearing impairment or normal hearing, was found to be significant (p<0.001) on mental health score. The results also showed that the mental health of individuals with hearing impairment was significantly poorer than normal hearing, hearing impairment with hearing aid was also significantly poorer than normal. Whereas, the mental health of hearing impairment was found to be worse than hearing impairment with hearing aids. Mental health of partners with hearing impairment was significantly poorer than normal hearing, hearing impairment with hearing aid was also significantly poorer than normal. Whereas, the mental health of hearing impairment was found to be worse than hearing impairment with hearing aids. In Conclusion higher the degree of hearing loss, the more severe the mental health symptom. The result showed that, the main effect of the group, i.e., individuals with hearing impairment with hearing aids, hearing impairment, or normal hearing, was found to be significant (p<0.001 on marital adjustment score.